A model for simulating the performance and irrigation of green stormwater facilities at residential scales in semiarid and Mediterranean regions. (September 2017) - Herrera, Josefina; Bonilla, Carlos A.; Castro, Lina; Vera, Sergio; Reyes, Rodolfo; Gironás, Jorge
Abstract: Impervious areas change hydrological processes, reducing infiltration and evapotranspiration, and increasing direct runoff. Stormwater practices using green infrastructure are implemented locally to control runoff and preserve the hydrological cycle. Applying these techniques in semiarid and Mediterranean regions requires accounting for aspects related to the maintenance of green areas. This study develops the Integrated Hydrological Model at Residential Scale, a continuous model for representing the performance and irrigation of green stormwater facilities at residential scales. Among other relevant process, the model simulates evaporation from bare soil and redistribution between soil layers. Different components of the model were tested using laboratory and numerical experiments, and then an application to a case study and a sensitivity analysis were carried out. The model identifies significant differences in the performance of a rain garden with different vegetation, climate and irrigation practices and provides good insight for the maintenance needs of green infrastructure for runoff control. Highlights: We develop a model to study hydrologic processes and irrigation at residential scales. Surface and subsurface processes and soil water content are continuously simulated. The main components were tested using laboratory and numerical experiments. Major differences due to vegetation type, climates and irrigation are identified. A MS Excel and Matlab package with the model is freely available for the community.